Strategi Guru Aqidah Akhlak dalam Membiasakan Adab Berbusana Peserta Didik - Meliana, Multi; Murniyetti, Murniyetti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The background of this research is that many of the clothes worn by students in madrasas and outside madrasas are not in accordance with Islamic teachings. There are many reasons, ranging from the social environment to social media, which make these clothes a trend for students. Therefore it is necessary to have guidance from various parties so that students are accustomed to wearing clothes based on Islamic teachings. One of them is the teacher's strategy carried out in madrasas. The purpose of this study is the teacher's strategy for Aqidah Akhlak in getting used to the etiquette of dressing for class XI IPA 2 students at MAN Lima Puluh Kota. This study used descriptive qualitative research methods with research informants: madrasa heads, Aqidah Akhlak teachers, and students in class XI IPA 2. Data collection techniques used observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this study indicate that the Akidah Akhlak teacher's strategy in familiarizing students with dress etiquette is: a) providing knowledge about Muslim dress etiquette, b) the teacher is a role model in dress, c) reprimand d) advice, e) giving sanctions.